PHRASEOLOGICAL TRANSLATION COMPARATIVE ANALYSIS ON THE BASIS OF TRANSLATIONS OF THE BOOK TAMBURLAINE THE CONQUEROR - Ахунбабаева Наргиза Хамиджановна; Абдусамиева Л. Н. (Journal Park Publishing, 2025)
The main purpose of the article is a phraseological interpretation comparative analysis on the basis of the translations of the book «Tamburlaine the conqueror» in Uzbek and Russian languages. Pragmatic orientation research of phraseological units in a literary text has been conducted in order to define the phraseological expressions’ additional, implicit meaning plus its appropriate translation was analyzed and discussed on the basis of some bright examples of phraseological units used in the original and the translations as well.
Keywords: Research, phraseological units, translation, pragmatic, text, define, implicit, analyzed, original.